PENINGKATAN MOTIVASI DAN HASIL BELAJAR EKONOMI DENGAN TEAM GAME TOURNAMENT (TGT) - Mas Indah (Madaris: Jurnal Guru Inovatif, 2022)
This research was conducted to determine the increase in motivation and learning outcomes of students in class X IPS 2 at MAN 2 Bantul after participating in the learning process by applying the Team Game Tournament (TGT) type cooperative learning model. This study uses observation to determine learning motivation, and tests to determine student learning outcomes. The results showed that the learning process using the Team Game Tournament was as follows; In cycle 1 to cycle 2 the percentage of students whose learning motivation is in the low category continues to decline, namely 40.08% - 15.52%, the middle category is the same as 35.34%, and the high category is from 27.58% - 49.14 %. Learning outcomes also increased from the initial conditions, cycle 1, and cycle 2 (41.38% - 62.07% - 86.21%). Action is said to be successful if at least the percentage of students whose learning motivation is still low only reaches a maximum of 20%. The average score of students at the end of the cycle who scored below the KKM only reached a maximum of 20%. So this CAR is stated to have succeeded in increasing motivation and learning outcomes.